Cardiovascular pathology - Buja, L. Maximilian; Butany, Jagdish (Academic Press is an imprint of Elsevier, 2016)
Cardiovascular Pathology, Fourth Edition, provides users with a comprehensive overview that encompasses its examination, cardiac structure, both normal and physiologically altered, and a multitude of abnormalities. This updated edition offers current views on interventions, both medical and surgical, and the pathology related to them. Congenital heart disease and its pathobiology are covered in some depth, as are vasculitis and neoplasias. Each section has been revised to reflect new discoveries in clinical and molecular pathology, with new chapters updated and written with a practical approach, especially with regards to the discussion of pathophysiology. New chapters reflect recent technological advances with cardiac devices, transplants, genetics, and immunology. Each chapter is highly illustrated and covers contemporary aspects of the disease processes, including a section on the role of molecular diagnostics and cytogenetics as specifically related to cardiovascular pathology.